1995
DOI: 10.1139/o95-065
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal ganglion cell axons after optic nerve crush: neurofilament expression is not the sole determinant of calibre

Abstract: After injury in the central nervous system of adult mammals, many of the axons that remain attached to their intact cell bodies degenerate and decrease in calibre. To understand this process better, we have investigated the relationship between axonal loss, cell loss, and the time course of changes in axonal calibre. Optic nerves (ONs) were crushed and the numbers and sizes of axons remaining close to the cell bodies (2 mm from the eye) and near the site of the lesion (6 mm from the eye) were determined for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Decreased caliber of about 40-45% begins at proximal levels of the regenerating stump and is later also seen at a more distal level, consistent with the possibility that this percentage of the total neurofilament has been transported anterogradely out of the atrophied portions of the axon. Under the same conditions of suppressed NF synthesis, the smaller ventral motor axons (32) and all transected optic axons (33) undergo no change in caliber or neurofilament content, as predicted if most neurofilaments in these axons are stationary. Based on previous data.…”
Section: Reconciling Old and New Findingsmentioning
confidence: 58%
See 2 more Smart Citations
“…Decreased caliber of about 40-45% begins at proximal levels of the regenerating stump and is later also seen at a more distal level, consistent with the possibility that this percentage of the total neurofilament has been transported anterogradely out of the atrophied portions of the axon. Under the same conditions of suppressed NF synthesis, the smaller ventral motor axons (32) and all transected optic axons (33) undergo no change in caliber or neurofilament content, as predicted if most neurofilaments in these axons are stationary. Based on previous data.…”
Section: Reconciling Old and New Findingsmentioning
confidence: 58%
“…Based on previous data. (32,33) isotypes undergoing transport is much smaller than the preexisting (and presumably stationary) pool in the axon.…”
Section: Reconciling Old and New Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…Optic nerve crush induced injury to the optic nerve and loss of viable axons, [185][186][187] which led to retrograde degeneration of RGC in the rat and mouse. Depending on the force used during the crush, a wide spectrum of RGC damage, ranging from practically no change in cell density to almost complete elimination of the cells within 30 days, were achieved.…”
Section: Optic Nerve Injurymentioning
confidence: 99%
“…It has been shown that optic nerve crush induces optic nerve injury and causes retrograde degeneration of RGC of the rat. 17 Optic nerve crush model is easy to perform and it causes slow RGC loss that is much more similar to the nature of glaucoma than that of optic nerve transection model. Optic nerve damage may be induced by crushing optic nerve with clamps, forceps or other mechanic devices.…”
Section: Discussionmentioning
confidence: 99%